Answer:
a)-5
Step-by-step explanation:
-(5-(a+1))=9-(5-(2a-3))
= -(5-a-1)= 9-(5-2a+3)
= -5+a+1 = 9-5+2a-3
= -4+a = 1+2a
= -4 - 1 = 2a-a
= -5 = a
b). 17feet
c). 1/34 feet
d). 34 feet
Answer:
Step-by-step explanation:
Given:
We need to find the inverse of f(x).
Step 1: Set f(x) = y
Step 2: Switch x and y
Step 3: Solve for y, Isolate y
Multiply by 9 both sides
Add 2 both sides
Hence,
********************************
12y = 8
y =
given y ∝ x
To convert to an equation multiply by k the constant of variation
y = kx
to find k use the given condition y = 6 when x = 72
y = kx ⇒ k = = =
equation is → y = x
when x = 8 then
y = × 8 = =
As a starter, the y value is equal to f(x); the x value is equal to the x in f(x).
So basically, in this case, replace x with the number in the brackets.
Coordinates have x, y values (x, y). Here, we know x is -2, so we need to find y.
on the graph, find x = -2 and find where the line of the drawn graph intersects it. Looks like the line intersect x = -2 when y = 3. So f(-2) = 3.
Same applies for b: x = 0, find where the line hits x = 0, and that's your y value, which is 1.
Tried my best to simplify it. Hope it helps lol.